FINANCIAL PERFORMANCE DIFFERENCES BETWEEN CONVENTIONAL AND ISLAMIC BANKS IN INDONESIA - Dwi Laela Ardiyanti (COMPETITIVE, 2026)
Banking institutions play a crucial role in maintaining financial stability and public trust. Differences in operational principles between conventional and Islamic banks may result in variations in financial performance. This study examines whether significant differences exist in the financial performance of conventional and Islamic banks listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative comparative approach was employed using secondary data from 15 conventional banks and 4 Islamic banks selected through purposive sampling. Financial performance was measured using Return on Assets (ROA), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), and Operating Expenses to Operating Income (BOPO). Data were analyzed using normality tests, independent sample t-tests, and Mann–Whitney tests. The findings reveal significant differences in ROA, CAR, and BOPO (p < 0.05), indicating variations in profitability, capital adequacy, and operational efficiency. However, no significant differences were found in LDR and NPL, suggesting similarities in liquidity management and credit risk. These results indicate that differences in business models influence profitability and efficiency, while regulatory harmonization contributes to similar liquidity and credit risk performance across banking systems.